Synthesis, photophysical properties and biological evaluation of β-alkylaminoporphyrin for photodynamic therapy. Issue 22 (15th November 2016) - Liao, Ping-Yong; Wang, Xin-Rong; Gao, Ying-Hua; Zhang, Xiang-Hua; Zhang, Li-Jun; Song, Chun-Hong; Zhang, Dan-Ping; Yan, Yi-Jia; Chen, Zhi-Long
Graphical abstract: CompoundD6 is an effective and a highly promising antitumor agent for photodynamic therapy. Highlights: A series of β-alkylaminoporphyrins were synthesized. They exhibited low dark toxicity and excellent phototoxicity against HeLa cells. D6 showed the highest phototoxicity and the lowest dark toxicity. D6 exhibited best photodynamic antitumor efficacy on BALB/c nude mice. D6 is a powerful and promising antitumor photosensitizer for PDT. Abstract: A series of β-alkylaminoporphyrins conjugated with different amines at β position (D1 –D3 ) or with electron-donating and electron-withdrawing substituents at phenyl position (D4 –D6 ) were synthesized. Their photophysical and photochemical properties, intracellular localization, photocytotoxicities in vitro and vivo were also investigated. All target compounds exhibited no cytotoxicities in the dark and excellent photocytotoxicities against HeLa cells. Among them, D6 showed the highest phototoxicity and the lowest dark toxicity, which was more phototoxic than Hematoporphyrin monomethyl ether (HMME ). In addition, D6 exhibited best photodynamic antitumor efficacy on BALB/c nude mice bearing HeLa tumor. Therefore, D6 is a powerful and promising antitumor photosensitizer for photodynamic therapy.